HUBUNGAN KOMUNIKASI ANGGOTA KELOMPOK DENGAN KINERJA PETANI JAGUNG DI DESA AMESIU KECAMATAN PONDIDAHA KABUPATEN KONAWE - Sulastri, Anci; Wunawarsih, Ima Astuty; Lasinta, Megafirmawanti; Isnian, Sitti Nur (Jurusan Penyuluhan Pertanian FP UHO, 2025)
The objective of this study is to ascertain the correlation between the efficacy of group communication and the performance of corn farmers in Amesiu Village, Pondidaha District, Konawe Regency. The research population consists of all corn farmer groups in Amesiu Village, with a total of 12 groups comprising 180 corn farmers. The sample size was determined using the Slovin formula with a margin of error of 10%, resulting in a sample of 64 respondents. The data were collected through a combination of interviews, documentation, and surveys, with questionnaires serving as the primary instruments. The research variables of interest were group member communication and corn farmer performance. The research data was then subjected to quantitative analysis. This analysis method was carried out in two ways: descriptive analysis and Spearman's rank correlation analysis. The results indicated that the communication exhibited by the corn farmer group was classified within the